Monascus-Fermented Dioscorea Enhances Oxidative Stress Resistance via DAF-16/FOXO in Caenorhabditis elegans - Shi, Yeu-Ching (Public Library of Science, 2012)

(untitled)
BACKGROUND: Monascus-fermented products are mentioned in an ancient Chinese pharmacopoeia of medicinal food and herbs. Monascus-fermented products offer valuable therapeutic benefits and have been extensively used in East Asia for several centuries. Several biological activities of Monascus-fermented products were recently described, and the extract of Monascus-fermented products showed strong antioxidant activity of scavenging DPPH radicals. To evaluate whether Monascus-fermented dioscorea products have potential as nutritional supplements, Monascus-fermented dioscorea’s modulation of oxidative-stress resistance and associated regulatory mechanisms in Caenorhabditis elegans were investigated. PRINCIPAL FINDINGS: We examined oxidative stress resistance of the ethanol extract of red mold dioscorea (RMDE) in C. elegans, and found that RMDE-treated wild-type C. elegans showed an increased survival during juglone-induced oxidative stress compared to untreated controls, whereas the antioxidant phenotype was absent from a daf-16 mutant. In addition, the RMDE reduced the level of intracellular reactive oxygen species in C. elegans. Finally, the RMDE affected the subcellular distribution of the FOXO transcription factor, DAF-16, in C. elegans and induced the expression of the sod-3 antioxidative gene. CONCLUSIONS: These findings suggest that the RMDE acts as an antioxidative stress agent and thus may have potential as a nutritional supplement. Further studies in C. elegans suggest that the antioxidant effect of RMDE is mediated via regulation of the DAF-16/FOXO-dependent pathway.